Expression of the Drosophila homeobox gene, Distal‐less, supports an ancestral role in neural development. Issue 1 (3rd November 2015) - Plavicki, Jessica S.; Squirrell, Jayne M.; Eliceiri, Kevin W.; Boekhoff‐Falk, Grace
Abstract : Background: Distal‐less ( Dll ) encodes a homeodomain transcription factor expressed in developing appendages of organisms throughout metazoan phylogeny. Based on earlier observations in the limbless nematode Caenorhabditis elegans and the primitive chordate amphioxus, it was proposed that Dll had an ancestral function in nervous system development. Consistent with this hypothesis, Dll is necessary for the development of both peripheral and central components of the Drosophila olfactory system. Furthermore, vertebrate homologs of Dll, the Dlx genes, play critical roles in mammalian brain development.Results: Using fluorescent immunohistochemistry of fixed samples and multiphoton microscopy of living Drosophila embryos, we show that Dll is expressed in the embryonic, larval and adult central nervous system and peripheral nervous system (PNS) in embryonic and larval neurons, brain and ventral nerve cord glia, as well as in PNS structures associated with chemosensation. In adult flies, Dll expression is expressed in the optic lobes, central brain regions and the antennal lobes.Conclusions: Characterization of Dll expression in the developing nervous system supports a role of Dll in neural development and function and establishes an important basis for determining the specific functional roles of Dll in Drosophila development and for comparative studies of Drosophila Dll functions with those of its vertebrate counterparts. Developmental Dynamics 245:87–95, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: This is the first detailed description of Distal‐less expression throughout embryonic, larval and adult stages with a particular focus on the nervous system. We provide substantial support for the ∼20 year old proposal that the ancestral function of Distal‐less was in the nervous system and facilitate future use of Drosophila to investigate how Distal‐less functions during differentiation of neural structures.